(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the potential protective effect of pumpkin seed oil (PSO) against Carbon tetrachloride Induced Hepatotoxicity in Albino Rats. Study Design: Experimental study Place and Duration of Study: This study was conducted at the Department of Anatomy, Pharmacology and Pathology, SRMC, T. Adam from March 2019 to January 2020. Materials and Methods: 100 rats were divided equally into five groups. Group A negative control and Group B (positive control) (CCl4 (0.2 mL/kg), Group C – CCl4 (0.2 mL/kg) + PSO (1 mL/Kg bwt), Group D –CCl4 (0.2 mL/kg+ PSO (2 mL/Kg) and Group E– CCl4 (0.2 mL/kg)+(PSO (3 mL/Kg). Carbon tetrachloride was administered intraperitoneal at a dose of 0.2 mL/kg twice a week and PSO for 8 weeks. Blood samples were collected from the retro – orbital capillary plexus after anesthesia. Sera were used for the biochemical analysis; liver function tests (spectrophotometric), superoxide dismutase, glutathione peroxidase and catalase were detected by ELISA assay. Data was analyzed on statistical SPSS package (ver. 21.0) at 95% Confidence interval. Results: We observed carbon tetrachloride (CCl4) induced hepatotoxicity was improved significantly after 8 weeks pumpkin seed oil (PSO). Serum bilirubin, PT, ALT, AST and GGT were mitigated significantly (P≤ 0.0005). Pumpkin seed oil (PSO) augmented the superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT) activity after 8 weeks therapy (P≤ 0.0005). Conclusion: The present study reports hepatoprotective potential of pumpkin seed oil against carbon tetrachloride induced hepatotoxicity in male Wistar albino rats.